Substitution Uterus Between Permission A Substitution Uterusnd ProhibitionIn The light of The Legitimate Rules - علوان, سلام خليل (Journal of College of Education, 2018)
The supstitutional pregnancy is to fertilize a woman's egg with the sperm of a man who is vaccinated  externally in a test container and then fertilize the fertilized egg  in  the  Uterus  of  any  other  woman      who carries it to the birth of the fetus, either by voluntary or coerced pregnancy, whether it is a fetus or not .                                                               Some scientists call this process a lethargy, pregnancy, pregnancy, uterine Uterus, or supstitutional Uterus pregnancy, which I see as the most appropriate name for this process is called the process of  uterus supstitutional, because there is no conflict between the name and its meaning,If the science will reach to manu fucture An external uterus is able to incubate the fetus at all stages, and the word Substitution Uterus includes all the elements that lead to reproduction are the sperm, egg and uterus.                                                The idea of Substitution Uterus arose as a result of IVF, as a means of treating infertility among those unable to conceive in normal ways.    The various images of uterus variant can be shown in eight pictures and each of these images has a provision of its own in terms of prevention or legal permission                                                                     The scholars differed concerning the ratios of the newborn in terms of the mother in the case of pregnancy with the supstitutional uterus. Some of them went to the fact that the mother is the owner of the egg, and the other part went to the fact that the real mother is the owner of the uterus and the first openion is the most likely .          The scholars  differed that the child is attributed to his father – the    husband of the egg woman - who was vaccinated with his liquid and is not attributed to the husband of the owner of the uterus. Although there is no genetic relationship between them, and does not follow the husband's semen, and the first is the most likely.